2017
DOI: 10.1590/1414-431x20176036
|View full text |Cite
|
Sign up to set email alerts
|

An ontogenic study of the behavioral effects of chronic intermittent exposure to ayahuasca in mice

Abstract: Ayahuasca is a beverage obtained from decoctions of the Banisteriopsis caapi plus Psychotria viridis. In religious contexts, ayahuasca is used by different age groups. However, little is known of the effects of ayahuasca during ontogenic development, particularly with regard to the functional characteristics of the central nervous system. Animal models are useful for studying the ontogenic effects of ayahuasca because they allow exclusion of the behavioral influence associated with the ritualistic use. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Durante os encontros das religiões que utilizam ayahuasca em rituais, que ocorrem com frequência, a bebida é ingerida entre os participantes variando de uma a três doses durante a cerimônia. Em um estudo realizado por Santos et al,(2017) foi estudado o uso crônico da ayahuasca em animais e os riscos relacionados a exposição diária e por longos períodos. Os autores encontraram que, para o maleficio e/ou letalidade, é necessários que sejam ingeridas doses 50 vezes maior do que normalmente é utilizado.…”
Section: Resultados E Discussõesunclassified
“…Durante os encontros das religiões que utilizam ayahuasca em rituais, que ocorrem com frequência, a bebida é ingerida entre os participantes variando de uma a três doses durante a cerimônia. Em um estudo realizado por Santos et al,(2017) foi estudado o uso crônico da ayahuasca em animais e os riscos relacionados a exposição diária e por longos períodos. Os autores encontraram que, para o maleficio e/ou letalidade, é necessários que sejam ingeridas doses 50 vezes maior do que normalmente é utilizado.…”
Section: Resultados E Discussõesunclassified
“…Mice in different stages of the development treated twice a week with ayahuasca (1.5ml/kg[1x]) had no locomotor activity alteration in the open field, tested one day after administration (t[14 to 20]=-1.8456 to 1.1527, p=0.084 to 0.804); however, ayahuasca-treated infant mice spent more time in risk assessment behaviour in the elevated plus-maze test, suggesting increased anxiety (t[19]=-3.2684; p=0.004), and adolescents spent less time in and crossed fewer times the platform quadrant of the Morris water maze (t[20]=-2.6937 and -2.3350, p<0.05), indicating a memory impairment (Correa-Netto et al, 2017b). Using the same dose, ayahuasca administration twice a week in six-month-old mice for one year did not alter ageing or anxiety parameters evaluated by open field, elevated plus maze, and Morris water maze test (all p>0.05) tested before the start of treatment and one day after the last administration (Correa-Netto et al, 2017a).…”
Section: General Behavioural Mental Health Model and Cognition (N=17)mentioning
confidence: 99%
“…[221][222][223] However, others found that ayahuasca administration reduced anxiety. [224][225][226] Additionally, investigations in zebrafish revealed anxiogenic behavior following ayahuasca administration. 227,228 Substance misuse…”
Section: Anxiety and Panic-like Disordersmentioning
confidence: 99%